Bringing history to life through film : the art of cinematic storytelling - Morey, Kathryn Anne, 1987- (Film and History., 2014)
This collection of essays addresses important questions about the relationship between fact and fiction: When does history become myth, and when does myth become legend? Does a romanticized view of history distort the reality it is trying to convey, or in capturing the "spirit" of history, does it teach history in ways that mere fact cannot? What is the impact of motion pictures on our understandings of history and on historical memory? And what of the lives of the individuals it portrays? These essays introduce arguments about how storytelling within a film can help the viewer und.